The specificity of ten non-digestible carbohydrates to enhance butyrate-producing bacteria and butyrate production in vitro fermentation - Jingjing Xu; Ruyue Wang; Weibao Liu; Zhongwei Yin; Jianrong Wu; Xun Yu; Wen Wang; Hongtao Zhang; Zhitao Li; Minjie Gao; Li Zhu; Xiaobei Zhan (Food Science and Human Wellness, 2023)
Butyrate and butyrate-producing bacteria are important indicators of gut microbial metabolism in human health. Ten non-digestible carbohydrates (NDCs), including inulin, fructooligosaccharide (FOS), oats β-glucans (OGS), oats β-glucan oligosaccharides (OGOS), Astragalus polysaccharides (APS), Astragalus oligosaccharides (AOS), xanthan gum oligosaccharides (XGOS), gellan gum oligosaccharides (GGOS), curdlan oligosaccharides (COS), and pullulan oligosaccharides (POS) were used to investigate NDC specificity in modulating butyrate-producing bacteria and butyrate production in 48-h in vitro fermentation studies in combination with fecal inocula from 7 healthy donors and 11 patients with type 2 diabetes (T2D). We observed that the amount of these ten NDCs utilized depended on NDC structure and inter-individual gut microbial differences. XGOS and GGOS fermentations significantly increased butyrate-producing bacteria (especially f_Lachnospiraceae) and butyric acid production. Furthermore, XGOS and GGOS fermentations showed a better ability to consistently modulate gut microbiota composition and metabolic properties between individuals of healthy donors or T2D patients when compared to inulin, FOS, APS, AOS, OGS, OGOS, COS and POS fermentation. This research indicated that xanthan gum and gellan gum oligosaccharides have strong specificity to enhance butyrate-producing bacteria and butyrate production.